Efektivitas Sistem Pengendalian Intern Atas Prosedur Penerimaan Dan Pengeluaran Kas Lembaga Pendidikan - Sri Melati Nababan; Nusa Muktiadji (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
James Education Center is one of the companies engaged in education. Internal control is a plan, method, procedure, and policy designed by management to provide adequate assurance on the creation of operational efficiency and effectiveness, control of financial reporting, security of assets, compliance/compliance with laws, and regulatory policies. This study aims to determine the effectiveness or ineffectiveness of the James Education Center's internal cash receipts and disbursements control system and to identify the cash receipts and disbursements system. Based on the results of the study, it can be said that all the rules in the internal control system for cash receipts and disbursements procedures are not in accordance with the applicable rules. Keywords: Effectiveness, Internal Control, Cash Receipts and Disbursements